2014
DOI: 10.1378/chest.13-1432
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Supplementation During Pregnancy and Respiratory Symptoms in Children

Abstract: BACKGROUND:Prenatal consumption of omega-3 fatty acids can act as an adjuvant in the development of the immune system and aff ect the infl ammatory response of neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…After removal of duplicates and title/abstract screening, the remaining 79 full text papers were assessed against the eligibility criteria for this systematic review. Ten publications from nine unique RCTs were included in the final analyses, including a total of 3,637 children (21,28,30,32,34,38,43,47,48,50) . In the case of one trial (29) , both the reports of an earlier (28) as well as latest follow-up data (47) were included, since some of the allergic outcomes of interest for this systematic review were reported only in the earlier published paper of this trial i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of duplicates and title/abstract screening, the remaining 79 full text papers were assessed against the eligibility criteria for this systematic review. Ten publications from nine unique RCTs were included in the final analyses, including a total of 3,637 children (21,28,30,32,34,38,43,47,48,50) . In the case of one trial (29) , both the reports of an earlier (28) as well as latest follow-up data (47) were included, since some of the allergic outcomes of interest for this systematic review were reported only in the earlier published paper of this trial i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Four trials were conducted on high-risk (atopy) populations (21,32,34,38) and the remainder (28,30,43,47,48,50) were carried out on sample with low-risk allergies. The sample size of studies at randomisation were also varied, from 98 (21) to 1,094 (43) pregnant women.…”
Section: Participants and Sample Sizesmentioning
confidence: 99%
“…A more recent large randomized study of prenatal omega-3 fatty acid supplementation found that prenatal DHA supplementation compared with vegetable oil supplementation decreased atopic eczema and sensitization to egg [4]. Similarly, a follow-up study of 869 children found that DHA supplementation significantly reduced respiratory symptoms among children born to atopic mothers; although, paradoxically, respiratory symptoms were increased among children born to DHA-supplemented non-atopic mothers [10] Our hypothesis that omega-3 fatty acid supplementation may function in neonatal immune modulation is supported by these studies.…”
Section: Introductionmentioning
confidence: 99%
“…We choose this n ‐3 PUFA supplementation dose because it was similar to those given for human study supplementation (Escamilla‐Nuñez et al . ). Furthermore, the enriched diet was designed to obtain an omega‐3/omega‐6 ratio near 1 (Table ), which is commonly recommended (Simopoulos, ).…”
Section: Methodsmentioning
confidence: 97%